Aspectos do controle de resíduos de avermectinas no abate de bovinos - Prata, Camila Barbieri [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Changes in international food controls aiming their safety occurred with the change of the century, based on the Risk Analysis and Hazard Analysis and Critical Control Points. For chemical residues, although a pre-existing problem, the situation only gained notoriety after 2010, with the presence of avermectin residues in Brazilian meat products exported to the United States and European Union. Since then, several mitigation measures were incorporated in the routine set of self-controls the processing companies.This work aimed to verify the practicality and effectiveness of these measures for effective control of processes, segregating slaughtered animals that could contribute to unacceptable levels of risk, based on monitoring of avermectins residues in two sample matrices, liver and muscle of cattle slaughtered. For the muscle matrix were analyzed 81,565 batches of animals, with 1,153 or 1.41% batches whose residues were above the avermectin MRL (Maximum Residue Level) of 10μg/kg during the years 2010 and 2011. from 2012 was used the liver matrix , with 77,056 samples being analyzed. Of these, 29,267 or 37.98% were positive for residues, with 4,602 or 5.97% above the MRL of 100μg/kg. The analytical results shown so far, the aggravation of problems at the primary link of the production chain of Brazilian beef

As mudanças nos controles internacionais dos alimentos visando sua inocuidade se efetivaram com a mudança de século, tendo como base a Análise de Riscos e a Análise de Perigos e Pontos Críticos de Controle. Para os resíduos químicos, apesar de problema pré-existente, a situação só ganhou notoriedade a partir de 2010 com a detecção da presença de resíduos de avermectinas em produtos cárneos brasileiros exportados para os Estados Unidos e União Europeia. A partir de então, várias medidas de mitigação foram inseridas no conjunto rotineiro de autocontroles pelas empresas processadoras. Neste trabalho objetivou-se verificar a praticidade e eficácia dessas medidas para o controle efetivo dos processos, segregando animais abatidos que pudessem contribuir para níveis inaceitáveis do perigo, com base na monitoração de resíduos de avermectinas em duas matrizes amostrais, fígado e músculo de bovinos abatidos. Para a matriz músculo foram analisados 81.565 lotes de animais, com 1,41% desses ou 1.153 lotes que apresentaram resíduos de avermectinas superiores ao LMR de 10μg/kg durante os anos de 2010 e 2011. A partir de 2012 utilizou-se a matriz fígado, sendo analisadas 77.056 amostras. Dessas, 29.267 ou 37,98% apresentaram positividade para resíduos, sendo que 4.602 ou 5,97% foram superiores ao LMR de 100μg/kg. Os resultados analíticos demonstram, até agora, agravamento do problema no elo primário da produção de carne bovina brasileira
Keywords: Bovino; Lactonas; Figado; Musculos; Resíduos; Carne - Qualidade; Lactones